Leucine-Specific, Functional Interactions between Human Immunodeficiency Virus Type 1 Nef and Adaptor Protein Complexes - Coleman, Scott H. (American Society for Microbiology, 2005)
The human immunodeficiency virus type 1 virulence protein Nef interacts with the endosomal sorting machinery via a leucine-based motif. Similar sequences within the cytoplasmic domains of cellular transmembrane proteins bind to the adaptor protein (AP) complexes of coated vesicles to modulate protein traffic, but the molecular basis of the interactions between these motifs and the heterotetrameric complexes is controversial. To identify the target of the Nef leucine motif, the native sequence was replaced with either leucine- or tyrosine-based AP-binding sequences from cellular proteins, and the interactions with AP subunits were correlated with function. Tyrosine motifs predictably modulated the interactions between Nef and the μ subunits of AP-1, AP-2, and AP-3; heterologous leucine motifs caused little change in these interactions. Conversely, leucine motifs mediated a ternary interaction between Nef and hemicomplexes containing the σ1 plus γ subunits of AP-1 or the σ3 plus δ subunits of AP-3, whereas tyrosine motifs did not. Similarly, only leucine motifs supported the Nef-mediated association of AP-1 and AP-3 with endosomal membranes in cells treated with brefeldin A. Functionally, Nef proteins containing leucine motifs down-regulated CD4 from the cell surface and enhanced viral replication, whereas those containing tyrosine motifs were inactive. Apparently, the interaction of Nef with the μ subunits of AP complexes is insufficient for function. A leucine-specific mode of interaction that likely involves AP hemicomplexes is further required for Nef activity. The μ and hemicomplex interactions may cooperate to yield high avidity binding of AP complexes to Nef. This binding likely underlies the unusual ability of Nef to induce the stabilization of these complexes on endosomal membranes, an activity that correlates with enhancement of viral replication.